New species and new country records for Neotropical Cerambycinae (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2023)
Three new species of Cerambycidae (Coleoptera) are described and illustrated: Lingafelterellus barclayi sp. nov. (Elaphidiini), from Ecuador; Neocompsa obliqua sp. nov. (Tropidini, Compsina), from Mexico; and Odontogracilis mudgei sp. nov. (Rhinotragini), from Mexico. An updated key to species to Lingafelterellus is provided. Neocompsa obliqua sp. nov. is included in a previous key. New country records are provided for: Criodion tuberculatum Gahan, 1892; Juiaparus batus batus (Linnaeus, 1758); Eburodacrys nemorivaga Gounelle, 1909; Compsibidion vanum (Thomson, 1867); and Tropidion fairmairei (Gounelle, 1909).